A systematic review and meta-analysis of substance use and attention deficit hyperactivity disorder - Eustace-Cook, Jessica; Comiskey, Catherine; Banka-Cullen, Sonam; James, Philip; Lavelle Cafferkey, Sadie; McDonagh, David (My University, 2025)
The World Health Organization defines neurodevelopmental disorders as cognitive and behavioural conditions arising during a child's development. These include autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). ADHD involves a persistent pattern of inattention and/or hyperactivity-impulsivity, negatively affecting academic, occupational, or social functioning. ASD includes difficulties with social communication and interaction, alongside repetitive and inflexible behaviours, interests, or activities. There is a growing shift to emphasise biopsychosocial protective factors, especially in the context of increasing co-morbidity between neurodiversity and substance use disorders. The aim of this study was to provide up to date estimates of the prevalence of neurodiversity among people accessing addiction services internationally and in Ireland and to identify the risk and protective factors to inform appropriate service responses. The research used a mixed methods study design, with the data being collected concurrently. A review of the international literature was conducted systematically. A quantitative component collected anonymous survey data online from the general population. Qualitative data was collected at two levels: qualitative survey questions with the public, and qualitative data collected from ten organisations who provide support to people with substance use challenges and their families in both Dublin city and rural locations. From the international literature a total of 154 estimates, from 32 countries dated from 1997 to 2024 were included. The meta-analysis consisted of a global sample of 56,632 individuals who were known to have used a range of substances and who were subsequently assessed for ADHD using either a clinical interview or the Adult ADHD Self-Report Scale (ASRS) screening instrument. The sample contained a minimum of 29,303 males and 13,004 females. The overall estimate of the prevalence of ADHD within this population of people who used substances was found to be 21% with a very narrow confidence interval, reflecting the large sample size used within the meta-analysis (95% CI of 20.6% to 21.3%). When comparing rates across genders and substances, the highest rate of ADHD overall was found amongst women using benzodiazepines, this was estimated to be 39.5% (95% CI of 33.7% to 45.3%). The rates of ADHD were statistically significantly higher among males than females among those who use alcohol, who use cocaine and who use cannabis. Similarly, this study identified for the first time that the rates of ADHD are statistically significantly higher amongst females than males who used opiates. A total of 288 participants (171 females, 113 males and 4 non-binary) from all 26 counties completed the online survey with a mean age of 42 years and a range of 18 to 83 years. Almost 62% of the participants were either married or in a relationship. Almost three quarters (73%) had attained third level education and almost half (49%) were in full time employment. A total of 91 participants (32%) said they had been in treatment for drug or alcohol problems at some stage in their lives and 63 (22%) people said they were currently in some form of treatment for substance use, with 18 respondents attending multiple treatment services. The prevalence of ADHD among the survey participants was 51% with a 95% CI of 45% to 57%. Given gender, prevalence rates were 54% among males and 46% among females. The prevalence of ASD among the survey participants was 37% with a 95% CI of 32% to 43%. Given gender, the prevalence rates were 33% among males and 39% among females. A Pearsons Chi Squared test for association found a statistical difference between the heterosexual and LGBTQI+ groups, with the prevalence of ADHD (64%) higher among the LGBTQI+ group, (X2 (2, N = 288) = 8.527, p= .003). Furthermore, a Pearsons Chi Squared test also showed a significant difference between the heterosexual and LGBTQI+ groups for ASD, with the prevalence of ASD (57%) higher among the LGBTQI+ group, (X2 (2, N = 288) = 17.978, p< .001). A Mann Whitney U test demonstrated a significant difference between participants reporting and those not reporting substance dependence and their overall scores in the ADHD screening tool, (U = 1350.000, Z = -3.648, p< .001), with an average ADHD score of 15, indicating a risk of ADHD for those reporting substance dependent versus an average of 11 for those not reporting substance dependence. However, no significant difference was found between those with and without ADHD and problematic alcohol use as measured by the Audit C instrument (p=.366). Cannabis was the illicit substance with the most frequent use among the sample, it was used at least weekly by 82 (28%) of the respondents. Moreover, a Pearsons Chi Sq. test found a significant association between people using cannabis at least weekly and ADHD (X2 (1, N = 288) = 8.912, p= .003), with 64.6% of those using cannabis regularly having either a diagnosis of ADHD or screening positive for the condition. No significant association was found between ADHD and people who have spent time in treatment and those who have not (p= .054). This may indicate that people experiencing ADHD and are using 11 substances are not necessarily entering treatment services, although they may benefit from service given their substance use. From the qualitative interviews with service providers, it was found that the majority of service providers did not have any formal education or training in neurodiversity. Managing the needs of people who attend their services has been learned on the job using a trial-and-error approach. Communicating with and managing people with neurodiverse conditions provided a major challenge for service provider staff, particularly when providing services for people with ASD. For some service users it can take years to find an effective treatment programme based on their individual needs. Finally, the lack of a referral pathway through the Irish health system for adults who want to receive a formal diagnosis ADHD or ASD was a barrier. Providing appropriate support for those with mental health and drug and alcohol problems was raised by almost all the providers as a major issue for their service.
PUBLISHED